FOLFOX-HAIC combined with targeted immunotherapy for initially unresectable hepatocellular carcinoma: a real-world study - Lu, Yan-Cen; Yang, Yu-Chen; Ma, Di; Wang, Jun-qing; Hao, Feng-Jie; Chen, Xu-xiao; Chen, Yong-jun (Frontiers in Immunology, 2024)
BackgroundHepatic arterial infusion chemotherapy (HAIC) with the FOLFOX regimen has demonstrated efficacy in patients with unresectable hepatocellular carcinoma (HCC). The combined targeted and immunotherapy has emerged as a first-line treatment for liver cancer. In this study, we investigated the clinical efficacy and safety of FOLFOX-HAIC in combination with targeted immunotherapy in patients with untreated, unresectable HCC.Materials and methodsData were collected from patients with initially unresectable HCC treated at Ruijin Hospital, affiliated with Shanghai Jiao Tong University School of Medicine, from June 2022 to June 2023. Tumor response and survival outcomes were assessed following the FOLFOX-HAIC combined with targeted immunotherapy, The safety was also evaluated through the incidence of related adverse events.ResultsA total of 51 eligible patients were recruited. The objective response rate (ORR) based on mRECIST and RECIST 1.1 criteria were 60.8% and 45.1%, respectively. The surgical conversion rate was 25.5%. The median progression-free survival (PFS) was 15.2 months. The 1-year overall survival rate was 88.2%. Adverse events were observed in 98% patients, with 23.5% experiencing grade 3 or 4 adverse events.ConclusionThe FOLFOX-HAIC combined with targeted immunotherapy regimen is effective in patients with unresectable HCC, demonstrated by a high surgical conversion rate and manageable adverse effects. This regimen represents a potential novel first-line treatment option for HCC.